Eksistensi dan Fungsi Kampung (Lewo) dalam Pemerintahan Desa di Hinga Kecamatan Kelubagolit Kabupaten Flores Timur - Fikriansyah Kia Dore; Kotan Y. Stefanus; Rafael R. Tupen (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is motivated by the existence and function of the village (Lewo) in village government, which shows that the existence of a village as a village is still classified as a strong criterion. This is because the village (Lewo) can give identity to a village where the original face of the village is still visible, which is marked by the existence of customs that are still firmly attached. So that the formulation of the problem in this research: (1) How is the existence and function of the village (Lewo) in village governance? (2) What is the relevance of village (Lewo) in Village Administration? This research is normative legal research supported by empirical legal research. Aspects of research include the existence and function of the village (Lewo) in village administration, the relationship between the existence and function of the village (Lewo) and the village government in village government, the dynamics of the existence and function of the village (Lewo) with the village government in village governance. The results of the study show that: (1) The function of the village or lewotanah is carried out by a triad of collegial leadership consisting of landlords called Tanah alapen, village heads called mehene lewo, and customary priests called rerawulan alapen. The lewotanah leadership then formed a governance structure and placed leadership in each corner of lewotanah. (2) that the function of the village or lewotanah is carried out by a triumvirate of collegial leadership consisting of landlords called Tanah Alapen, village heads called mehene lewo, and customary priests called rera wulan alapen and other village functions are to assist the village government in solving problems that occurs between communities in order to maintain harmony between community members and assist the village government in village development.